Attabot 2.0: An Open-Source Educational Robot for Mechatronics and Robotics Studies - Ferreira Júnior, José Divino; Fonseca, João Paulo Da Silva; Tavares, José Jean Paul Zanlucchi De Souza (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
This paper presents an educational robot called Attabot 2.0, it is suitable for a broad range of academic levels, from elementary school to doctorate programs, focusing on in the field of mechatronics. The original Attabot was designed to assist ant pheromone algorithm in robot autonomous decision. The same project served as the basis for the development of a new robot with an educational focus. The paper presents the Attabot 2.0 project, and its key attributes includes low-cost nature, open-source design, fully integrated with Robot Operating System (ROS), and Internet of Things (IoT) technologies. Integration with ROS empowers students with advanced robotics capabilities, while IoT connectivity facilitates interaction with the physical world, where the student can interact with the robot from remote locations in case of social isolation requirements. With these attributes Attabot 2.0 is a viable option in the realm of affordable and open-source robotics education, offering a complete and cost-effective solution.